2021
DOI: 10.1097/ccm.0000000000005055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early Multiple Organ Dysfunction With Clinical and Functional Outcomes Over the Year Following Traumatic Brain Injury: A Transforming Research and Clinical Knowledge in Traumatic Brain Injury Study

Abstract: OBJECTIVES: Traumatic brain injury is a leading cause of death and disability in the United States. While the impact of early multiple organ dysfunction syndrome has been studied in many critical care paradigms, the clinical impact of early multiple organ dysfunction syndrome in traumatic brain injury is poorly understood. We examined the incidence and impact of early multiple organ dysfunction syndrome on clinical, functional, and disability outcomes over the year following traumatic brain injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The Glasgow Outcome Scale (GOS) recorded, at hospital discharge the male presented, the lowest values (GOS 2 and GOS 3) and they are consistent with other studies [16,17,21,22] it found an association of sex patients with the mechanisms of injury, the level of severity and the length of hospital stay. Besides, GOS one year after hospital discharge was similar to the reported by other studies [21,22] that indicated a pathophysiological response of the brain to trauma which was higher in children and young people.…”
Section: Discussionsupporting
confidence: 89%
“…The Glasgow Outcome Scale (GOS) recorded, at hospital discharge the male presented, the lowest values (GOS 2 and GOS 3) and they are consistent with other studies [16,17,21,22] it found an association of sex patients with the mechanisms of injury, the level of severity and the length of hospital stay. Besides, GOS one year after hospital discharge was similar to the reported by other studies [21,22] that indicated a pathophysiological response of the brain to trauma which was higher in children and young people.…”
Section: Discussionsupporting
confidence: 89%
“…MODS, which has been estimated to occur in more than two-thirds of sTBI patients, can lead to several contraindications to NWT. [ 52 , 65 ] Neuromonitoring can indirectly detect neuroworsening through evaluating the physiologic state of brain tissue in some of these difficult scenarios. [ 19 , 57 ] In particular, recent evidence has pointed to a survival benefit of using brain tissue oxygen (B tp O 2 ) monitoring.…”
Section: Identifying Neuroworseningmentioning
confidence: 99%
“…The incidence of nonneurological organ dysfunction developing in TBI patients is 33%-89%. [1][2][3][4] Among various kinds of organ dysfunction, acute kidney injury (AKI) has attracted wide attention, due to its unfavorable effects on cerebral edema and prognosis of TBI patients. Both injury severity and inappropriate medical strategy can promote the development of AKI in TBI patients.…”
Section: Introductionmentioning
confidence: 99%